Multiple myeloma—A painful disease of the bone marrow. (April 2021) - Diaz-delCastillo, Marta; Chantry, Andrew D.; Lawson, Michelle A.; Heegaard, Anne-Marie
Abstract: Multiple myeloma is a bone marrow neoplasia with an incidence of 6/100, 000/year in Europe. While the disease remains incurable, the development of novel treatments such as autologous stem cell transplantation, proteasome inhibitors and monoclonal antibodies has led to an increasing subset of patients living with long-term myeloma. However, more than two thirds of patients suffer from bone pain, often described as severe, and knowledge on the pain mechanisms and its effect on their health-related quality of life (HRQoL) is limited. In this review, we discuss the mechanisms of myeloma bone disease, the currently available anti-myeloma treatments and the lessons learnt from clinical studies regarding HRQoL in myeloma patients. Moreover, we discuss the mechanisms of cancer-induced bone pain and the knowledge that animal models of myeloma-induced bone pain can provide to identify novel analgesic targets. To date, information regarding bone pain and HRQoL in myeloma patients is still scarce and an effort should be made to use standardised questionnaires to assess patient-reported outcomes that allow inter-study comparisons of the available clinical data.